2014
DOI: 10.1186/s12711-014-0060-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of principal component regression and genomic REML for genomic prediction across populations

Abstract: BackgroundGenomic prediction faces two main statistical problems: multicollinearity and n ≪ p (many fewer observations than predictor variables). Principal component (PC) analysis is a multivariate statistical method that is often used to address these problems. The objective of this study was to compare the performance of PC regression (PCR) for genomic prediction with that of a commonly used REML model with a genomic relationship matrix (GREML) and to investigate the full potential of PCR for genomic predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…PLS. The effect of various methods for extracting and selecting PCs in PCR for predicting genomic breeding values in cattle has been investigated by Dadousis et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…PLS. The effect of various methods for extracting and selecting PCs in PCR for predicting genomic breeding values in cattle has been investigated by Dadousis et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that reduction in computational complexity via multivariate methods did not counterbalance their lower accuracy compared with BayesB. Accuracies of genomic predictions obtained using PCR and G-BLUP models was also investigated by Dadousis et al ( 2014 ), who reported across test datasets and traits, G-BLUP outperformed the PCR model. However, in the present study Bayesian estimation of effects and variances of PC scores led to accuracies similar to BayesB and better accuracies than PCR-Eigen where PC variances were proportional to the eigenvalues.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the estimation accuracy no longer improves as the SNP density increasing. The reason may be that there is a high degree of linkage disequilibrium among higher density SNPs, which is manifested as multicollinearity in statistics (Dadousis et al, 2014). There is a general correlation in the selected SNPs, and the results obtained are similar to a certain extent (Kuehn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%